The effect of the method and the timing of the propagation on the growth, earliness and productivity of sweet corn - Hodossi, S.; Kovács, A.; Besenyei, E. (International Journal of Horticultural Science, 2000)
Direct sowing in 16 cm deep trench covered with perforated plastic sheet (for 3 weeks), transplant using, and uncovered direct sowing (control) was tried on 2 locations, with 2 varieties (very early Kecskeméti korai extra, and middle early Kecskeméti SC-370) in Szarvas on loamy soil, and in Kecskemét on sandy soil in 1996 — after a preliminary trial concerning perforated plastic covered trench sowing in Szarvas, in 1995.The plant height (weekly), the average leaf number/plant, the total leaf area (once), the total yield, the quality of cobs, and the earliness was measured. The results are:• Kecskeméti korai extra during the first 6 week period the transplanted plants were the highest, but from the 7th week the plants which were sown in trench and than were covered with perforated plastic sheet (for 3 weeks) were the highest.• SC-370: The transplanted plants were the highest-until the end of plant height development.The plant height development stopped at the 9th week of the measurement by early, - and stopped at the 10th week by middle early variety. The average leaf number/plant varied between 9,25-10,50 and was not influenced either by variety or by the treatment. The total leaf area was (on 5th of June) the largest by transplanted plants, which was followed by plants that were sown in trench and then were covered with perforated plastic film (for 3 weeks).• The highest yield was observed by plants, which Were sown in trench, and then were covered with perforated plastic film (for 3 weeks). Transplanted plants followed it.• Quite the total yield (98,3%) of transplanted Kecskeméti korai extra variety plants were harvested on 4th July. 89% of the total yield was picked up of trench sown and then with perforated plastic covered plants. The harvest of uncovered control started on 15th July. The harvest of transplanted SC-370 plants started 19th July, when more than half of the total yield (57%) was picked. The uncovered control was harvested 29th July.• The weight and the measure of cobs generally were not influenced by the treatments, but the average weight of the cobs of the transplanted Kecskeméti korai extra plants (0,21-0,18 kg) are less than the, requirement.